Prognostic value of CD169-positive macrophages in various tumors: a meta-analysis. Issue 1 (1st January 2021) - Kong, Weihao; Wei, Meng; Liu, Rongqiang; Zhang, Jianlin; Wang, Xingyu
ABSTRACT: The study aimed to evaluate the prognostic value of CD169 expression in tumor-infiltrating macrophages from regional lymph nodes (RLN) in various tumors. In order to identify eligible articles, PubMed, EMBASE, Web of Science, and Cochrane Library were used to conduct a systematic search. Pooled hazard ratios (HRs) or odds ratios (ORs) with corresponding 95% confidence intervals (CIs) were adopted to assess the relationship between CD169 expression and overall survival (OS) and clinicopathological characteristics. Ten studies, including eleven cohorts with 1699 patients, were enrolled. We found that high CD169 + expression in tumor-infiltrating macrophages from RLN was associated with a favorable OS (HR = 0.56, 95%CI: 0.39–0.79, P = 0.001). Subgroup analysis showed that high CD169+ expression had more predictive power in digestive system tumors (HR = 0.52, 95%CI: 0.42–0.67, <0.001). In addition, high CD169 expression was significantly linked with lymph node metastasis (OR = 0.66, 95%CI: 0.47–0.94, P = 0.020) and TNM stage (OR = 0.62, 95%CI: 0.48–0.80, P < 0.001). High CD169 expression in tumor-infiltrating macrophages from RLN was correlated with favorable survival outcome in patients with malignancies. CD169 may be a novel and effective prognostic marker, especially for digestive system tumors. GRAPHICAL ABSTRACT: uf0001